Mental Illness and its Link to Illegal Street Market Activity: Prevalence, Risk Factors, and How They Compare to Violence. (September 2021) - Harris, Michelle N.; Daigle, Leah E.
Given the focus on research assessing violence among people with mental illness, other forms of deviance such as illegal street market offending have been relatively ignored. As such, the prevalence and risk factors for illegal street market offending among those with mental disorders is unknown. Utilizing the MacArthur Risk Assessment Study, the prevalence of illegal street market offending among this population is assessed along with the risk factors for engaging in this type of behavior. These factors are investigated for their generality in predicting violent offending to see if there are unique risk factors associated with illegal street market offending. Results indicate that factors related to money, factors related to substance usage, and general factors related to offending are significantly associated with illegal street market offending. Theoretical implications and future research are discussed.